OP0184 High Resolution Micro-Computerized Tomography Imaging as a Translational Tool to Quantitatively Assess Bone Damage in a Mouse Model of Collagen-Induced Arthritis in Mice: Disease Severity and Time-Course of Bone Changes. (23rd January 2014) - de Garavilla, L.; Acton, P.; Lubomirski, M.; Malaviya, R.; Shen, F.; Shah, N.; Vasquez, S.; Yoder, V.; Small, D.; Weinstein, D.; Kilgore, K.
Abstract : Background: HR micro-CT is a powerful imaging tool to visualize and quantify the degree of bone damage in the preclinical and clinical setting, thus making it a highly translatable tool. Unlike flat-film radiography, CT imaging allows one to generate a 3-D reconstruction of the diseased joint providing one unparalleled images Objectives: 1) apply HR micro-CT imaging to the knee and ankle joints in a murine CIA model, 2) develop novel image analysis techniques to objectively quantify the degree of bone damage, 3) demonstrate that micro-CT imaging and the novel image analysis techniques can discriminate differences in the severity of bone damage in models of CIA and document a beneficial response to a therapeutic agent. Methods: CIA Model. Standard models of CIA were used to induce rheumatoid arthritis (RA) in male DBA/1J mice using both complete (CFA) and incomplete (IFA) Freud's adjuvant co-injected with bovine collagen. A sensitizing dose was injected on day 0 followed by a challenge on day 21. The control group 1 received PBS/PBS (day 0/day 21), group 2 and 3 received CFA/CFA and CFA/IFA, respectively, and group 4 received CFA/CFA plus therapeutic doses of dexamethasone (DEX). Body weight (BW), disease score and ankle thickness were scored. Mice were euthanized on day 40. The hind leg was perfused with formalin and excised above the knee and stored in formalin for CT imaging. Results: Clinically, BW was reduced in all groups from day 21 to day 40, except PBS control group. Clinical scores and paw thickness were significantly greater in groups 2 (CFA/CFA) and 3 (CFA/IFA), although the CFA/CFA group showed the more severe changes of the two. Shown in the figure is a diseased ankle from a mouse in group 2. Powerful and discreet image analysis techniques were applied to the raw grey-scale images to derive the corresponding color-coded images that were used to provide highly quantitative and objective measures of bone disease, in this case highlighting SR (blue is no SR and red/yellow is high degree of SR). Bone SR was 10.8±0.45, 18.17±5.25, 14.6±5.35 and 11.85±0.49 in the ankle, and 6.99±0.38, 10.86±2.69, 8.29±2.69 and 6.53±0.28 in the knee for groups 1, 2, 3 and 4, respectively. Interestingly, the knee joint showed a greater sensitivity to changes in SR as compared to the ankle. BD in the distal tibia was significantly less in group 2 as compared to the control and DEX-treated groups. Image/graph: Conclusions: Micro-CT imaging is a powerful translational tool to assess bone damage in RA. Image analysis techniques, including SR and BD, can be successfully used to objectively quantify bone damage. These advances will allow investigators and drug developers to more effectively predict the bone sparing or protective effects of newer therapeutic agents used to treat RA. Acknowledgements: We acknowledge the technical assistance of Shannon Hichcock. Disclosure of Interest: None Declared